Prakiraan Cuaca Dengan Menggunakan Metode Naive Bayes Classifier - Azhar, Joehari; Syaharani, Widya (Yayasan Pendidikan Al-Yasiriyah Bersaudara, 2024)
Weather forecasting is one of the important areas in human life. Planning, transportation, agriculture, and tourism are just a few of the uses for weather forecasts. Weather forecasting is the process of predicting future weather conditions. Various methods exist for weather forecasting, including manual and computer-based methods. The manual calculation process for weather prediction still lacks accuracy, so researchers conducted a study to develop a simple system that can produce more accurate weather predictions. The method used in this study is a Naïve Bayes classifier by using training data as data for an event from previously known facts or reality. The final test results, conducted on a simple system and compared with manual calculations, demonstrated a higher level of accuracy.